Independent and state school partnerships (ISSPs) in England: systemic tensions and contemporary policy resolutions. (3rd April 2022) - Hunnaball, Margaret; Jones, Jane; Maguire, Meg
ABSTRACT: English education has a long-standing parallel but unequal school system. State-maintained schools are free of charge for attendees; independent schools are free from state control and funded largely by fees. Most independent schools hold charitable status which benefits them in relation to taxation although they cater largely for socially advantaged students. Various governments have enacted different policies to try to rebalance some of these systemic educational tensions. This paper examines how the independent and state school partnerships (ISSP) policy seeks to rebalance, or provide some compensation for, independent schools' charitable status through the requirement that they provide 'public benefit'. In ISSPs, schools from the two sectors work together on dedicated activities, sharing resources and expertise. Drawing on data from three telling cases, we argue that ISSP policy may deliver some localised benefits to both types of schools but that these relationships are unlikely to produce any major structural changes.